The Influence of Leadership Style, Work Motivation, and Compensation on the Performance of MSME Center Employees in Semarang City - Suheri, Kasih Febrina; Raharjo, Susilo Toto (Master of Management, Faculty of Economics and Business, Diponegoro University, 2023)
This study aims to test and analyze the influence of leadership style, work motivation, and compensation on employee performance at the Semarang City MSME Center. This research was motivated by the emergence of employee dissatisfaction during the reorganization. Many factors trigger employee dissatisfaction in carrying out work, including those related to leadership qualities that have not been in line with expectations. In addition, the turmoil that arises comes from leadership that is less capable. The purpose of this study is to analyze the influence of leadership, work motivation and compensation on job satisfaction of MSME Center employees in Semarang City. The population determined in this study is UMKM Center Semarang. This study involved 75 respondents using census / saturated sample techniques. The instrument used in this study was in the form of a questionnaire and in its measurement in the form of a Likert scale, by testing it using the help of SPSS. Data testing techniques used in this study include validity test with factor analysis, reliability test with Alpha Cronbach. Test classical assumptions and multiple linear regression analysis, to test and prove research hypotheses. The results of this study show that leadership has a positive and insignificant effect on employee performance. Meanwhile, work motivation and compensation have a positive and significant effect on the performance of MSME Center employees in Semarang City.